Pediatric dermatofibrosarcoma protuberans: A clinicopathologic and genetic analysis of 66 cases in the largest institution in Southwest China - Zhang, Zhang; Lu, Yang; Shi, Changle; Chen, Min; He, Xin; Zhang, Hongying (Frontiers in Oncology, 2023)
Background Dermatofibrosarcoma protuberans (DFSP) is an uncommon cutaneous tumor in children. Most of published articles are sporadic or small cases and lack systematic molecular analyses. The aim of our study is to better understand the clinicopathologic and genetic features of these rare lesions. Methods All patients diagnosed as DFSP with aged ≤ 18 years were retrospectively reviewed from January 2006 to May 2022. Results A total of 66 cases (32 males and 34 females) of cases were identified, with age ranging from 0.3 to 18 years (median 13 years). Tumor locations predominantly occurred at trunk (38/66, 57.6%), followed by extremities (20/66, 30.3%), head/neck (8/66, 12.1%). Histological findings revealed classic (41/66, 62.1%), myxoid (4/66, 6.1%), pigmented (6/66, 9.1%), plaque-like (3/66, 4.5%), giant cell fibroblastoma (GCF; 6/66, 9.1%), and fibrosarcomatous (6/66, 9.1%) variants of DFSP. Immunochemistry revealed minority (9/64, 14.0%) showed patchy or negative staining for CD34. Fluorescence in situ hybridization (FISH) indicated 49 of 53 tested cases including all detected biopsy specimens (11/11) contained COL1A1-PDGFB fusion which the average copy number gains of COL1A1-PDGFB was 0.68. There were 4 cases negative for COL1A1-PDGFB, one of which was found to harbor a novel COL3A1-PDGFB fusion by next-generation sequencing (NGS). Treatment for 63 patients comprised 40 marginal excisions and 23 wide excisions, including 1 with imatinib therapy. Follow-up information was available on 49 patients with duration from 12-161 months (median 60 months). Fourteen patients developed tumor recurrence all with initially marginal excisions. The others survived with no evidence of disease. Conclusions The large series of pediatric DFSP study indicates certain discrepancy of clinicopathologic characteristics between children and adults. There are majority of pediatric DFSP contains COL1A1-PDGFB fusion same as adults, while presents lower level of the average COL1A1-PDGFB copy gains than the adult counterpart. Moreover, this article describes the first example of DFSP harboring COL3A1-PDGFB fusion. FISH is valuable in assisting diagnoses of biopsy tissues and cases with atypical CD34 immunostaining, while supplementary NGS could be helpful to identify the cytogenetically cryptic DFSP. Overall, it is urgent for an accurate diagnosis to make an optimal therapeutic strategy in the special population.